Towards Equitable Inclusion for Refugees: The Needs of Students With and Seeking Refugee Protection - Schutte, Valerie; Milley, Peter (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2023)
Despite data increasingly being used to advance equity in education, students with and seeking refugee protection (SWSRP) are largely invisible in education data. To equitably include SWSRP in national education systems as envisioned by global refugee education policy, data on their needs are required. The purpose of this study was to source, organize, and analyze data on the needs of SWSRP in primary and secondary education in Canada. This needs assessment involved the use of experts, a selective review of empirical literature, and a review of publicly available data. Five common areas of need were identified among SWSRP globally and across Canada’s 13 primary and secondary education systems: access to education, accelerated education, language education, mental health and psychosocial support, and special education. Rates of needs varied by a range of student experiences and circumstances. These data can inform efforts to responsively support SWSRP in Canadian education systems.